Identification of amino acid residues in the ligand binding repeats of LDL receptor important for PCSK9 binding - Deng, Shi-jun (J Lipid Res, 2019)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) promotes LDL receptor (LDLR) degradation, increasing plasma levels of LDL cholesterol and the risk of cardiovascular disease. We have previously shown that, in addition to the epidermal growth factor precursor homology repeat-A of LDLR, at least three ligand-binding repeats (LRs) of LDLR are required for PCSK9-promoted LDLR degradation. However, how exactly the LRs contribute to PCSK9’s action on the receptor is not completely understood. Here, we found that substitution of Asp at position 172 in the linker between the LR4 and LR5 of full-length LDLR with Asn (D172N) reduced PCSK9 binding at pH 7.4 (mimic cell surface), but not at pH 6.0 (mimic endosomal environment). On the other hand, mutation of Asp at position 203 in the LR5 of full-length LDLR to Asn (D203N) significantly reduced PCSK9 binding at both pH 7.4 and pH 6.0. D203N also significantly reduced the ability of LDLR to mediate cellular LDL uptake, whereas D172N had no detectable effect. These findings indicate that amino acid residues in the LRs of LDLR play an important role in PCSK9 binding to the receptor.